2018
DOI: 10.5935/0004-2749.20180022
|View full text |Cite
|
Sign up to set email alerts
|

Intracameral moxifloxacin after cataract surgery: a prospective study

Abstract: The results suggest moxifloxacin is a safe option for intracameral use after cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…We did not consider the intracameral use of moxifloxacin or vancomycin due to potential toxicity and local regulations. The available formulations of moxifloxacin in Brazil contain preservatives and adjuvants that are toxic to ocular structures 20 ; even the most used eye drops in our country (Vigamox®, Alcon), market as not having preservatives, has a warning that the solution should not be injected under the conjunctiva, nor introduced directly into the anterior chamber of the eye 20 , 21 . Other studies performed in other locations have, however, shown good results on its use, safety, and efficacy 16 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…We did not consider the intracameral use of moxifloxacin or vancomycin due to potential toxicity and local regulations. The available formulations of moxifloxacin in Brazil contain preservatives and adjuvants that are toxic to ocular structures 20 ; even the most used eye drops in our country (Vigamox®, Alcon), market as not having preservatives, has a warning that the solution should not be injected under the conjunctiva, nor introduced directly into the anterior chamber of the eye 20 , 21 . Other studies performed in other locations have, however, shown good results on its use, safety, and efficacy 16 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Moxifloxacin hydrochloride (MOX) is often the drug of choice, as it has been shown to have higher intraocular bioavailability compared to other fluoroquinolones 3,20 . However, overall limitations in drug absorption with eye drops mean that prophylactic antibiotic drops still must be used three times or more per day 21,22 …”
Section: Introductionmentioning
confidence: 99%
“… 3 , 20 However, overall limitations in drug absorption with eye drops mean that prophylactic antibiotic drops still must be used three times or more per day. 21 , 22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, a major clinical study by the European Society of Cataract and Refractive Surgeons (ESCRS) (3) demonstrated the benefits of intracameral cefuroxime. Recently, three Brazilian studies have demonstrated the safety and efficacy of intracameral moxifloxacin (4)(5)(6) . Nevertheless, the adoption of such scientifically-proven strategies in clinical practice is hindered by other factors.…”
mentioning
confidence: 99%